STANDARDIZATION OF THE CURRICULUM CONTENT IN THE GENERAL EDUCATION OF LITHUANIA: QUALITY VS CONTROL - Nagrockaitė, Šarūnė (Acta Paedagogica Vilnensia, 2012)
In the paper, the purpose of a standard for achievements in teaching/learning in general education of Lithuania according to four stages of standardization specified by P. Sahlberg is discussed. While analyzing the standardization of education in Western states, the theorist of education proposes to spotlight the following standardization stages of the curriculum content: 1) setting a standard for achievements in teaching/learning in general education programs; 2) centralization of assessment by unifying the assessment of achievements in teaching/learning; 3) assessment of teachers and schools according to the achievements in teaching/learning; 4) introduction of penalties or rewards for the achieved level of progress. On the basis of these stages, an attempt is made to define a standard for achievements in teaching/learning as the limits for the quality and the control dimension. The paper is mostly based on the analysis of primary sources (Lithuanian education policy documents) and a qualitative analysis of the interview data of the empirical research (interviewing the experts).Taking into consideration the stages of standardization of the curriculum content, proposed by P. Sahlberg, it may be stated that the process of standardization is implemented in the upper secondary education program, because only its centralized assessment provides conditions for making various comparative assessments on the national scale. An analysis of the Lithuanian education policy documents has shown that the first three stages of standardization of the curriculum content are more related to the quality assurance than to the process of control. However, a qualitative analysis of the interview data has shown the education experts to think that there is an indirect impact of education control, performed through penalties and rewards and also by using public ratings of schools and through the regulation of admission of students to higher education studies. Using this strategy, the public opinion on the quality of schools is formed. In addition, it predetermines the decisions of students and teachers concerning changes of the contents of education, for example, shortening the curriculum content and changing it in accordance with the requirements of the school final (state) examination. In this way, the teaching/learning process is aimed at the preparation for the final (state) examination, but not at the curriculum content.
Keywords: standard; curriculum content; assessment; quality of education; control